Avaliação da farinha de carne e ossos na alimentação de frangos de corte - De Filho, Faria [UNESP]; De Faria, [UNESP]; Junqueira, O. M. [UNESP]; Rizzo, M. P. [UNESP]; Araújo, L. F. [UNESP]; Araújo, C. S.S. [UNESP] (My University, 2002)
Fourteen hundred and forty day-old male chicks were used to evaluate the use of meat and bone meal (MBM) on performance and carcass yield of broilers. The experimental design was a 2×2×2 factorial random arrangement: inclusion levels of MBM (3 and 6%), types of MBM (37.51 and 41.58% of crude protein), metabolizable energy values for MBM according to prediction equations (NRC, 1994) or by Rostagno et al. (1994), plus a control diet without MBM, with four replicates of forty chickens each. Feed intake and body weight gain (WG) were influenced by inclusion levels of MBM, with higher WG when MBM was not used. The remaining performance characteristics were not altered by the factors studied. There was reduction in abdominal fat when MBM was not used. It was concluded that the performance was impaired due to the use of diets containing up to 6% of MBM when compared to corn-soybean meal diets.
Evaluation of meat and bone meal in broiler chickens feeding
Keywords: Broilers; Carcass yield; Meat and bone meal; Metabolizable energy; Performance